Simulation of modified simple boost control for Z-source inverter - Husodo, Budi Yanto (2013)
In this paper, a simple boost control with independence relation between modulation index and shoot-through duty ratio (modified simple boost) for z-source inverter is simulated and analysed using MATLAB/Simulink, as well as the simple boost and the maximum boost control methods. The simulation shows that the modified simple boost control, as well as the maximum boost control could utilize high modulation index to generate output voltage that requires high voltage gain. In turn, this may suppress the voltage stress on the devices of z-source inverter.